Delayed Diagnosis of Pharyngeal Perforation following Exploding Tyre Blast Barotrauma - Samantha M. Field; Joseph G. Manjaly; S. Krishan Ramdoo; Huw A. S. Jones; Taran S. Tatla (Case Reports in Otolaryngology)
Introduction. Pharyngoesophageal perforation secondary to barotrauma is a rare phenomenon that can have serious complications if identified late. It is challenging to detect due to nonspecific symptoms. We present a case in which detection proved difficult leading to delayed diagnosis. Case Report. A 27-year-old mechanic presented with haemoptysis, dysphonia, and odynophagia after a car tyre exploded in his face. Flexible nasoendoscopy (FNE) revealed blood in the pharynx, thought to represent mucosal haemorrhage. Initial treatment consisted of IV dexamethasone and antibiotics. After 3 days, odynophagia persisted prompting a CT scan. This revealed a defect in the posterior hypopharynx and surgical emphysema in the deep neck tissues. Contrast swallow confirmed posterior hypopharyngeal leak. NG feeding was commenced until repeated contrast swallow confirmed resolution of the defect. Discussion. Prompt nonsurgical management of pharyngoesophageal perforation has good outcomes but untreated perforation can have serious complications. FNE should be performed routinely, but only a contrast swallow can diagnose a functional perforation. Clinicians should have a high index of clinical suspicion when patients present with barotrauma and odynophagia. Patients should be kept nil by mouth until perforation has been excluded. Conclusion. When faced with cases of facial barotrauma, clinicians should have a low threshold for further imaging to exclude pharyngoesophageal perforation.